Absorption, disposition, metabolism and excretion of [14C]mizagliflozin, a novel selective SGLT1 inhibitor, in rats. (3rd April 2019) - Ohno, Hitoshi; Kojima, Yasunari; Harada, Hiroshi; Abe, Yoshikazu; Endo, Takuro; Kobayashi, Mamoru
Abstract: The pharmacokinetic and metabolite profiles of mizagliflozin, a novel selective sodium glucose co-transporter 1 inhibitor designed to act only in the intestine, were investigated in rats. Mizagliflozin administrated intravenously (0.3 mg/kg) and orally (3 mg/kg) declined with a short half-life (0.23 and 1.14 h, respectively). The absolute bioavailability was only 0.02%. Following intravenous administration of [ 14 C]mizagliflozin (0.3 mg/kg), radioactivity in plasma was also rapidly declined. Up to 24 h after oral administration of [ 14 C]mizagliflozin (1 mg/kg), radioactivity was recovered in the faeces (98.4%) and in the urine (0.8%). No remarkable accumulation of radioactivity in tissues was observed using tissue dissection technique and whole body autoradiography. Orally dosed [ 14 C]mizagliflozin was mostly metabolised to its aglycone, KP232, in the intestine. In the plasma, KP232 and its glucuronide were predominant. KP232 glucuronide was also prominent in the bile and was recovered as KP232 in the faeces possibly because of the deconjugation by gut microflora. Mizagliflozin was observed neither in the urine nor the faeces. These findings suggest that orally administered mizagliflozin is poorly absorbed, contributing to low systemic exposure; if absorbed, mizagliflozin is rapidly cleared from circulation.